1996
DOI: 10.3171/jns.1996.84.2.0166
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lumbar spinal stenosis by extensive unilateral decompression and contralateral autologous bone fusion: operative technique and results

Abstract: A new surgical technique for the treatment of lumbar spinal stenosis features extensive unilateral decompression with undercutting of the spinous process and, to preserve stability, uses contralateral autologous bone fusion of the spinous processes, laminae, and facets. The operation was performed in 29 patients over a 19-month period ending in December of 1991. All individuals had been unresponsive to conservative treatment and presented with low-back pain in addition to signs and symptoms consistent with neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 48 publications
0
51
0
1
Order By: Relevance
“…Less invasive procedures, such as unilateral partial hemilaminectomies with transmedian removal of the compressive elements, are being used more frequently for the decompression of lumbar spinal stenosis in elderly patients. 8 This procedure is of a shorter duration. Compared with laminectomy, a unilateral partial hemilaminectomy results in less injury to paraspinal structures and provides a sufficient decompression.…”
Section: Methods Of Decompression and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Less invasive procedures, such as unilateral partial hemilaminectomies with transmedian removal of the compressive elements, are being used more frequently for the decompression of lumbar spinal stenosis in elderly patients. 8 This procedure is of a shorter duration. Compared with laminectomy, a unilateral partial hemilaminectomy results in less injury to paraspinal structures and provides a sufficient decompression.…”
Section: Methods Of Decompression and Outcomementioning
confidence: 99%
“…The surgical armamentarium includes procedures such as interspinous spacer implantation 2 and different kinds of unilateral and bilateral partial or full hemilaminectomies. 8 Nowadays, it is not very clear which of the techniques in practice is the most favorable. There are also results that did not confirm longterm effects of surgery when compared with conservative treatment only.…”
mentioning
confidence: 99%
“…Besides extensive procedures of laminectomy, bilateral multilevel fenestration and bilateral fenestration restricted to the clinically relevant level have been used [2,4,7,13,17,18,24,29,32,35,41,43]. Some fenestration studies are focused on the symptomatic stenotic side and if present, the contralateral asymptomatic but stenotic lateral recess is ignored [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…[9,18,21,26,30,49,50,52] Spinal fusion, PLIF in particular, is technically more demanding to perform than decompressive surgery. Potential long-term consequences of segmental fusion, notably accelerated adjacent-level degeneration, must be further investigated and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent, well-designed studies underscore the need for more effective treatments and outcome measures. [18,39,40,51,[68][69][70] Katz and associates [39] prospectively studied 194 patients treated with decompressive laminectomy for degenerative lumbar stenosis and reported that 22% of patients were somewhat or very dissatisfied with the results of surgery 6 months postoperatively. McCullen, et al, [50] reviewing 118 patients who underwent lumbar decompression for acquired spinal stenosis, reported 50% good, 27% fair, and 23% poor outcomes with an overall reoperation rate of 9%.…”
Section: Discussionmentioning
confidence: 99%